Evaluating Estrogen Receptor Signaling in Pancreatic β-Cells - Dover, Ellen Nicole (Wake Forest University, 2015)
Estrogen receptor signaling is involved in the etiology of multiple diseases including the development and progression of Type 2 Diabetes Mellitus, T2DM. The role of estrogen receptor signaling in peripheral insulin resistance has been shown through studies in post-menopausal women; however, estrogen receptor signaling in the β-cell is less understood. Conflicting data have arisen that demonstrate estrogen receptor signaling in the β-cell has either no effect, a protective effect against induced stress, or deleterious effects after long term activation of signaling. The present study aimed to elucidate the role of estrogen receptor isoform and variant signaling on the health and function of pancreatic β-cells. The variants of ERα differ in the presence of two activation function (AF) domains, which regulate transcriptional activities. ERα66 possesses both domains, ERα46 lacks the AF-1 domain, and ERα36 lacks both the AF-1 and AF-2 domains. Expression of ERα66 induced constitutive ERE-dependent transcriptional activity, which was correlated to an increase in pancreatic β-cell death as observed through high throughput imaging analysis and apoptotic endpoint assays (caspase 3/7). ERα46 expression resulted in increased transcriptional and caspase 3/7 activity similar to ERα66. Interestingly, in all assays ERα46 was more sensitive to ligand treatment than ERα66, suggesting an inherent difference in the ligand responsiveness between these two variants in the INS-1E cell line. ERα36 did not significantly alter transcriptional or caspase 3/7 activity. Expression of the estrogen receptor isoform, ERβ, increased ERE-dependent transcriptional activity and caspase 3/7 activity, however the magnitude of activation was less than ERα. Expanding these assays into human islets revealed that raloxifene treatment results in a significant increase in insulin mRNA expression as well as differentially regulating genes that may be involved in β-cell health. In addition to testing isoforms and variants, coregulator interaction with the receptors was also assessed. The coregulator, NCoA5, significantly potentiated ERα66 activity, but had no significant effect on ERα46 or ERβ implying a dependence on the AF-1 domain. Overall, this study elucidates that genomic estrogen receptor signaling is deleterious to β-cell health and function.
Keywords: Diabetes; Estrogen Receptors; Estrogen Signaling; Nuclear Coregulators; Selective Estrogen Receptor Modulators; β-cells